Structural and biophysical correlation of anti-NANP antibodies with in vivo protection against P. falciparum - Tossapol Pholcharee (Nature Portfolio, 2021)
The most advanced P. falciparum circumsporozoite protein (PfCSP)-based malaria vaccine confers partial protection. Here, Pholcharee et al. present crystal structures, binding affinities/kinetics, and in vivo protection of 8 anti-NANP antibodies to understand in vivo protection of PfCSP-targeting antibodies.